Extended reality in anesthesia: a narrative review - Sung Hee Han; Kristen L Kiroff; Sakura Kinjo (Korean Journal of Anesthesiology)
The application of extended reality (XR) technology is rapidly expanding in the medical field, including anesthesia. This review aims to introduce the current literature on XR utilization to help anesthesiologists adopt this technology in education and clinical practice. XR is useful for both knowledge acquisition and skill training in a wide range of settings, from students to medical professionals. One of its major benefits is harm reduction through simulation scenarios that allow for immersion in clinical situations and opportunities to practice procedures and tasks. These scenarios often involve both technical and non-technical skills, enabling clinicians to enhance their capabilities without risking patient safety. In clinical settings, XR can also be used with patients to increase familiarity with medical procedures, provide education, and reduce anxiety. XR can also serve as a distraction technique, diverting the patient’s attention from medical procedures and enhancing comfort, which may contribute to reduced opioid use. Although the potential benefits of XR in anesthesia have been reported in various educational and clinical contexts, challenges, such as limited financial reimbursement and restricted technical accessibility, remain. With further research and technological advancements, XR technology has the potential for widespread adoption in anesthesia practice.